Selection criteria for yield in eggplant (Solanum melongena L.) - Ossama Muhra, Maysoun M. Saleh,; Suliman, Zaeda Alsayd (Horticultural Biotechnology Research, 2019)
Nineteen genotypes of eggplant (Solanum melongena L.) were collected from different places in Syria for evaluating the selection criteria for yield parameters. Yield traits (days to 50% flowering, days to flower setting, days to maturity, plant height/cm at flowering stage, fruit weight/g, number of harvested plants and fruit yield per genotype/kg) were recorded in order to study the traits relations and to their direct and indirect effects via other traits on eggplant yield. Results showed that both plant height and number of harvested plants together with other morphological parameters had positive significant correlation with yield parameters, so it can be taken as selection criteria to increase final yield of eggplant.